The relationship between blue swimming crab (Portunus pelagicus) abundance and environmental parameters in Spermonde Archipelago - Muh Saleh Nurdin; Eniwati Eniwati; Teuku Fadlon Haser; Nur Hasanah (Gorontalo State University, 2020)
Management and conservation of the blue swimming crabs by the marine protected area method require the abundance and environmental parameter information of the blue swimming crab. The aim of this study is to analyze the changes in the relative abundance of the blue swimming crab and its environmental parameters. The study was conducted from March to July 2015, in the waters of Salemo Island, Spermonde Archipelago. The specimens were collected at the three fishing locations around the mangrove, seagrass, and coral reef ecosystems. The variable of relative abundance of the blue swimming crab is determined catch per effort. Samples of environmental parameters such as temperature and current speed are measured in situ. However, for the salinity, dissolved oxygen, ammonia, nitrate, plankton, and chlorophyll-a were analyzed in the laboratory. A comparison of the blue swimming crab abundance in each ecosystem was conducted by One Way ANOVA. Moreover, the relationship between blue swimming crab abundance with environmental parameters was analyzed by multiple regression. The results show that the blue swimming crab is abundant in the seagrass and coral reefs. The environmental parameter that significantly influences the abundance of the blue swimming crab is salinity. The suitable area for blue swimming carb protection based on abundances are seagrass and coral reef ecosystems.